(untitled) (The Pakistan Development Review, 2000)
The role of television as a powerful medium of communication is wellrecognised. This one material commodity has most dramatically influenced the social life of India. About 75 percent of India’s one billion people live in villages. Today, in rural India, television is considered as a necessity and it has become a large part of most villagers’ daily life. Johnson’s book is about the role that television plays in the process of social change in rural India. His focus of research has been primarily on the advertising and entertainment aspect of television in the context of village life as a whole.